Analysis of consumers purchase intention in commerce and services in the neighborhood and the Impact of Covid-19 - Aragão, Claudia Gomes de; Ferreira, Flavio Mangili; Silva, Hermes Moretti Ribeiro da; Gomes de Aragao Belé, Tiago (Produção, 2024)
Paper aims: To analyze the consumers intention to buy in commerce and services in the neighborhood, using the Theory of Planned Behavior (TPB) as a theoretical basis, analyzing the Attitude, the Subjective Norm, the Perceived Behavioral Control, and expanding the TPB through the influence on the Attitude of the Moral Attitude, Empathic Concern and the Impact of Covid-19. Originality: There are no studies on consumer buying behavior in commerce and neighborhood services in emerging countries, nor with this combination in the conceptual structure - TBP, Empathic Concern, Moral Attitude and the Impact of Covid-19. Research method: Data were collected from respondents, and analysis was performed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Main findings: The results indicate that the consumer's attitude towards buying in the neighborhood's commerce and services was positively and significantly influenced by the Moral Attitude and Impact of Covid-19 but not by Empathic Concern. Attitude, Subjective Norm, and Perceived Behavioral Control positively and significantly influence the intention to buy in neighborhood commerce and services. Implications for theory and practice: As a theoretical implication, the conceptual model extends the TBP, adding the dimensions of Empathic Concern, Moral Attitude, and the Impact of Covid-19 on Attitude. In practice, the study can help store managers, retailers, and marketing professionals in the sector incorporate specific actions to reach potential consumers and improve their results.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Buy intention; Covid-19; Local service; Neighborhood economy; Theory of planned behavior

Deodorization of post-consumer plastic waste fractions: A comparison of different washing media - Roosen, Martijn; Harinck, Lies; Ügdüler, Sibel; De Somer, Tobias; Hucks, Amaury Gauvain; Gomes de Aragao Belé, Tiago; Büttner, Andrea; Ragaert, Kim; Van Geem, Kevin M.; Dumoulin, Ann; De Meester, Steven (Science of the Total Environment, 2022)
An important impediment to the acceptance of recyclates into a broader market is their unwanted odor after reprocessing. Different types of washing procedures are already in place, but fundamental insights into the deodorization efficiencies of different washing media are still relatively scarce. Therefore, in this study, the deodorization efficiencies of different types of plastics after washing with different media were determined via gas chromatography and mass spectrometry analysis. A total of 169 compounds subdivided into various chemical classes, such as alkanes, terpenes, and oxygenated compounds, were detected across all packaging types. Around 60 compounds were detected on plastic bottles, and around 40 were detected on trays and films. Owing to the differences in physicochemical properties of odor compounds, different deodorization efficiencies were obtained with different washing media. Water and caustic soda were significantly more efficient for poly(ethylene terephthalate) bottles with deodorization efficiencies up to 80%, whereas for polyethylene (PE) and polypropylene bottles, the washing media were relatively inefficient (around 30–40%). Adding a detergent or an organic solvent could increase deodorization efficiencies by up to 70–90% for these packaging types. A similar trend was observed for PE films having deodorization efficiencies in the range of 40–50% when washing with water or caustic soda and around 70–80% when a detergent was added. Polystyrene trays were most effectively deodorized with a detergent, achieving efficiencies up to 67%. Hence, this study shows that optimal washing processes should be tailored to specific packaging types to further improve deodorization and to eventually be able to meet ambitious European recycling targets.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Circular economy; Deodorization; Gas chromatography; Plastics recycling; Post-consumer packaging; Volatile organic compounds

Mechanical recycling of printed flexible plastic packaging: The role of binders and pigments - Lisiecki, M.; Belé, Tiago; Ügdüler, S.; Fiorio, R.; Astrup, T. F.; De Meester, S.; Ragaert, K. (Journal of Hazardous Materials, 2024)
Low-density polyethylene (LDPE), extensively employed in flexible plastic packaging, often undergoes printing with inks. However, during the mechanical recycling of post-consumer waste, these inks act as contaminants, subsequently compromising the quality and usability of recycled material. To understand better exactly which ink components cause which effects, this study comprehensively assesses the thermal behavior of three organic pigments and two commonly utilised binders, correlated with the impact on the mechanical recycling of LDPE-based flexible plastic packaging. In this regard, the study focuses on four pivotal factors: processability, mechanical properties, aesthetic attributes, and volatile organic compound profiles. The results indicate that nitrocellulose, used as a binder, degrades during reprocessing, resulting in film discoloration and the emission of potentially odorous compounds. Conversely, pigments are found to be dispersed within droplets of polyurethane binder in LDPE recyclates, whilst reprocessing printed samples detrimentally affects film properties, notably dart drop impact resistance, strain at break, and the number of inclusions. Additionally, it is shown that both inks comprise components that emit volatile compounds during reprocessing: non-thermally stable components, nitrocellulose and pigment yellow PY13, as well as low-molecular weight molecules from polyurethane and by-products from wax, plasticisers, and additives.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Design for circularity; Mechanical recycling; Solvent-based ink